2019
DOI: 10.1080/23303131.2019.1672599
|View full text |Cite
|
Sign up to set email alerts
|

De-Implementation of Evidence-Based Interventions: Implications for Organizational and Managerial Research

Abstract: The science of implementing evidence-based interventions (EBIs) is being developed in social work and many other disciplines. Particular attention has been paid to whether, when, and how to de-implement an EBI if that intervention turns out to be harmful and/or a more effective/efficient EBI becomes available. Current research focuses on investigating how various environmental-, organizational-, provider-, and client-level factors influence the deimplementation process. Grounded in the HIV prevention field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, examining how the descriptive representation of staff with lived experience influences the service outputs and patient outcomes of SUD treatment clinics might be premature, given that very few studies have explored the descriptive representation phenomena using people’s lived experience as a focal identity or private actor–dominant service field as a case. Health and social science communities also discourage conducting such outcome-focused studies without sufficient evidence and thoughtful consideration of the potential impacts on users’ care experiences, service user–provider engagement, organizational contexts, and future research (Krumholz, 2008; Mosley et al., 2019; Pinto & Park, 2019). However, better understanding of the conditions for descriptive representation and positive perceptions of the representation potential of staff with lived experience (from the perspective of senior managers) will provide important grounds for investigating how they can make substantive differences in service users’ immediate care experience and long-term outcomes by serving as representatives of these vulnerable users.…”
mentioning
confidence: 99%
“…However, examining how the descriptive representation of staff with lived experience influences the service outputs and patient outcomes of SUD treatment clinics might be premature, given that very few studies have explored the descriptive representation phenomena using people’s lived experience as a focal identity or private actor–dominant service field as a case. Health and social science communities also discourage conducting such outcome-focused studies without sufficient evidence and thoughtful consideration of the potential impacts on users’ care experiences, service user–provider engagement, organizational contexts, and future research (Krumholz, 2008; Mosley et al., 2019; Pinto & Park, 2019). However, better understanding of the conditions for descriptive representation and positive perceptions of the representation potential of staff with lived experience (from the perspective of senior managers) will provide important grounds for investigating how they can make substantive differences in service users’ immediate care experience and long-term outcomes by serving as representatives of these vulnerable users.…”
mentioning
confidence: 99%
“…A longitudinal study by Pinto et al examined 379 HIV providers' experiences in New York City when the Centers for Disease Control and Prevention began to de-implement HIV prevention interventions that had been in place for 20 years in favor of more effective approaches that had better supporting evidence. The study found that the de-implementation of these interventions had some unintended negative consequences, including downsizing of staff due to decreased funding and a reduction in technical resources and assistance that had come from the intervention before it ended (29)(30)(31). A commentary on de-implementation by Norton and Chambers also discusses at length potential unintended negative consequences, including downsizing, loss of trust by intervention recipients, and loss of revenue, that can result from de-implementing low-value health interventions (22).…”
Section: Discussionmentioning
confidence: 99%
“…Professionals are unlikely to adopt innovation when there is an existing intervention that they are comfortable with, have been using for years, requires few resources, is established as part of professional culture or lore, is intuitive, and has become part of a classroom or other system (Prasad & Ioannidis, 2014). Debunking by providing strong peer-reviewed evidence demonstrating no positive or negative effects is the primary current method of de-implementation (Pinto & Park, 2019). There are mixed effects of de-bunking (Upvall & Bourgault, 2018).…”
Section: Features Of a Generic De-implementation Planmentioning
confidence: 99%